NS-065/NCNP-01: An Antisense Oligonucleotide for Potential Treatment of Exon 53 Skipping in Duchenne Muscular Dystrophy - Naoki Watanabe; Tetsuya Nagata; Youhei Satou; Satoru Masuda; Takashi Saito; Hidetoshi Kitagawa; Hirofumi Komaki; Kazuchika Takagaki; Shin'ichi Takeda (Elsevier, 2018)
Duchenne muscular dystrophy (DMD), the most common lethal heritable childhood disease, is caused by mutations in the DMD gene that result in the absence of functional dystrophin protein. Exon skipping mediated by antisense oligonucleotides has recently emerged as an effective approach for the restoration of dystrophin, and skipping of exon 51 of DMD has received accelerated approval. Identifying antisense sequences that can provide the highest possible skipping efficiency is crucial for future clinical applications. Herein, we systematically tested two-step antisense oligonucleotide walks along human DMD exon 53 in order to define sequence-dependent effects of antisense oligonucleotide binding sites in human rhabdomyosarcoma cell lines. The first rough whole-exon 53 walk enabled the identification of a target region, and a second walk of this region was used to determine an optimal antisense oligonucleotide sequence (NS-065/NCNP-01) for exon 53 skipping. This oligonucleotide strongly promoted exon 53 skipping in a dose-dependent manner during pre-mRNA splicing in rhabdomyosarcoma and DMD patient-derived cells, and it restored dystrophin protein levels in patient-derived cells. NS-065/NCNP-01, a phosphorodiamidate morpholino oligomer, appears to be a promising candidate for treating exon 53 skipping, and it is potentially applicable to 10.1% of patients with DMD. Keywords: Duchenne muscular dystrophy, dystrophin, exon 53, exon skipping, antisense therapeutics, morpholino